Effect of Inflammation on Molecular Targets and Drug Transporters - Sherif Hanafy; Ayman O.S. El-Kadi; Fakhreddin Jamali (Frontiers Media S.A., 2012)
Inflammation, the host's response to infection and injury, is associated with altered expression of genes such as metabolizing enzymes, transporters, receptors and plasma proteins. The purpose of the present work was to characterize the effect of inflammation on selected molecular targets and transporters that affect drugs' action and disposition. We have used rats with adjuvant arthritis (AA), an animal model of chronic inflammation. The AA group received 0.2 ml of 50 mg ml-1 Mycobacterium butyricum suspended in squalene into the tail base. On day 12, the rats were euthanized and their organs (heart, liver, kidneys and intestine) excised. Expression of Cav1.2, β1-AR, β2-AR, α1A-AR, Nav1.2, Nav1.6, Kv1.5, Kv2.1, Kv3.1, oatp1a1, oatp1a5, oatp1b2, oatp2b1, oatp4a1, oat2, oat3, oct1, mdr1a, bsep, mrp1, mrp3, mrp6, IL-1α, IFN-γ, iNOS, MCP-1, IL-10, Cox-1 and Cox-2 were determined by real time polymerase chain reaction (RT-PCR). Inflammation resulted in a significant reduction of oct1, oatp4a1 and mrp1 gene expression in the liver and oatp2b1, mrp6 and bsep gene expression in the kidney. Oatp4a1 and mdr1a were found to be significantly upregulated in rat heart. In conclusion, inflammation alters the gene expression of some mediators and drug transporters that can influence the behavior of drugs in the body and contribute to therapeutic failure. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.